Knowledge, attitudes, and practices among medical students toward depression management: a cross-sectional study in China - Wei Zhang; Xiaolin Wu; Mi Li; Guoli Wang; Yan Liu; Xin Zhang; Linxuan Zhang (Frontiers Media S.A., 2024)
BackgroundThe prevalence of depression among university and college students in China is nearly one-quarter. This study aimed to investigate the knowledge, attitudes and practices (KAP) among medical students toward depression management. Depression, a significant public health issue, has a substantial impact on students, with a reported prevalence of 23.8% among university and college students in China.MethodsThis web-based cross-sectional study was conducted between January 2023 and October 2023 at three medical universities in China. A self-administered questionnaire collected demographic information and assessed medical students' KAP on depression management.ResultsA total of 632 participants were enrolled in this study from three medical universities. Among them, 383 (60.60%) were female, and the participants were aged 20.17 years on average (SD ± 1.80). Most of their family members (521, 82.44%) were not in the medical profession. Using a validated 15-point knowledge scale, a 50-point attitude scale, and a 30-point practice scale, which covered areas such as symptom recognition, treatment approaches, and stigma related to depression, the mean knowledge, attitudes and practices scores were 10.55 ± 3.36 (possible range: 0-15), 41.72 ± 4.45 (possible range: 10-50) and 19.79 ± 5.44 (possible range: 6-30), respectively. Males had lower knowledge (p = 0.003). Only children had higher practice (p = 0.034). Urban residents had higher attitudes (p = 0.046). Higher income linked to better practice (p = 0.047). Freshmen scored higher across all KAP (p < 0.05). Medical family background linked to better knowledge (p = 0.005). The attitude scores were correlated with the practice scores (r = 0.403, p = 0.004). The structural equation model demonstrated that knowledge had direct effects on attitude and practice, as indicated by a path coefficient of 0.725 (p < 0.001) and 0.370 (p = 0.001), respectively. Furthermore, attitude had direct effects on practices, with a path coefficient of 0.509 (p < 0.001).ConclusionThe study revealed that medical students possessed sufficient knowledge and demonstrated active attitudes but exhibited limited practical skills in managing depression. In investigating the KAP of medical students, it is essential to integrate specific practical applications, such as role-playing scenarios and case studies, into the curriculum. These methods will emphasize the importance of knowledge, foster positive attitudes, and promote peer collaboration to enhance practical skills in depression management.